Factors Affecting Speech Delay In Toddlers - Farza Aulia; Hurun Ain; Nurul Pujiastuti (Journal of Nursing Science Update (JNSU), 2023)
The problem of speech delays in preschool children is estimated at 5% of the normal population. It is known that 19% of toddlers have speech and language development disorders, with details of 6.4% speech delay, 4.6% speech and language delay, and 6% language delay. This study aimed to identify factors associated with speech delay in toddlers. This study uses the Literature Review design. The article was taken from the SINTA, Garuda, PubMed, Science Direct, and Google Scholar databases with the keywords (((speech delay) AND toddler) AND influencing factors). The criteria for the articles used are 2018-2021 publications. The articles were selected using the PEOS framework and the JBI Critical Appraisal tools. The results showed that the factors that influenced the occurrence of speech delays included two articles related to gender, one article related to the incidence of physical trauma, two articles related to genetic factors, two articles related to neurological disorders, three articles related to the use of gadgets, and six articles related to parenting. Suggestions that further research can be carried out on the effect of implementing parenting patterns on speech delays in toddlers.